Legal Regulation on the Use of Online Learning Platforms: Challenges and Solutions in Indonesia - Indah Purnama Dewi; Mansyur Srisudarso (International Journal of Language and Ubiquitous Learning, 2024)
Background. With the rapid development of information technology, the use of online learning platforms in Indonesia is increasing. However, the legal regulations governing the use of these platforms are still limited and often inadequate. This poses a variety of challenges, including data security, copyright, and access equality issues. Purpose. This study aims to identify the challenges faced in the regulation of the use of online learning platforms in Indonesia and to formulate solutions that can be implemented to overcome these challenges. Method. This research uses a qualitative approach with literature study methods and in-depth interviews. The literature study was conducted to collect secondary data from various literature related to legal regulations and online learning platforms. In-depth interviews were conducted with experts in the fields of law, information technology, and education to gain deeper insights. Results. The results of the study show that the main challenges in regulating the use of online learning platforms in Indonesia include the lack of data security standards, weak copyright protection, and limited access for students in remote areas. In addition, the lack of coordination between relevant government agencies is also an obstacle to the effective implementation of regulations. Conclusion. This study concludes that to overcome the challenges in regulating the use of online learning platforms in Indonesia, comprehensive regulatory updates and better coordination between government agencies are needed. In addition, there is a need to increase awareness about the importance of data security and copyright among users and providers of online learning platforms. The implementation of these solutions is expected to increase effectiveness and fairness in the use of online learning platforms in Indonesia.